Survey and collection of aonla germplasm from eastern Uttar Pradesh (Indian Journal of Arid Horticulture, 2025)
Aonla (Emblica officinalis Gaertn) a member of family Euphorbiaceae is being cultivated in India since Vedic era. As a result of intensive research and developmental efforts aonla has attained a commercial status and proved to be a potential fruit crop for arid ecosystem. The fruit is recognized mainly for its nutritive, medicinal and high therapeutic properties (Shukla et al., 2002). The fruit is a rich source of vitamin-C and mainly grown in North India particularly Uttar Pradesh, Madhya Pradesh, Bihar, Rajasthan and Gujarat. Exploration was conducted during November 2004 to identify elite aonla genotypes of aonla from Vindhyan hills and part of eastern UP.
Keywords: Euphorbiaceae; therapeutic; aonla; Vedic era